Research Progress of MEMS Gas Sensors: A Comprehensive Review of Sensing Materials - Yingjun Wu; Ming Lei; Xiaohong Xia (Sensors)
The MEMS gas sensor is one of the most promising gas sensors nowadays due to its advantage of small size, low power consumption, and easy integration. It has been widely applied in energy components, portable devices, smart living, etc. The performance of the gas sensor is largely determined by the sensing materials, as well as the fabrication methods. In this review, recent research progress on H2, CO, NO2, H2S, and NH3 MEMS sensors is surveyed, and sensing materials such as metal oxide semiconductors, organic materials, and carbon materials, modification methods like construction of heterostructures, doping, and surface modification of noble metals, and fabrication methods including chemical vapor deposition (CVD), sputtering deposition (SD), etc., are summarized. The effect of materials and technology on the performance of the MEMS gas sensors are compared.